KONTROL DEBIT BANJIR BENDUNG DI KALI KUNING - Sutikno Lutjito (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2014)
ABSTRACTThis study aims to determine design–flood discharge that occur in existing dam at Kali Kuning riverand calculate flood discharge at 4 control points Chek Dam Kuning, Yapah, Ngadirojo andDadapan Weir. The background of this study is flood disaster at Kalikuning river.The study iscarriedout by hydrology and hydraulic analysis. The analysis of hydrology which included: testing ofconsistency data of rain fall, analysis of area averaged rain fall, design rain fall and testing ofgoodness of fit by using Smirnov-Kolmogorof test and chi square test. The analysis of hydrauliciscarried out by calculation the height ofthe design flood at each control pointusing Bundchuformulation. The study results show that for 5th rain fall recorder, namely Kaliurang, Pakem,Sorasan, Sopalan and Tanjungtirto using the Rational Method, Weduwen, and Hasperare obtainedthe flood discharge for 100 year return period as follows (1) Chek dam Kuning 129.253 m3/sec, (2)Yapah weir 226.697 m3/sec (3) Ngadirojo weir 262.062 m3/sec, (4) Dadapan weir 287.046 m3/sec.By using Bundchu formulation are obtained the overflow depth as follows: (1) 1.254 m, (2) 2,526m, (3) 2,163 m, (4) 3.157 m. The result explained that in Ngadirojo weir and Dadapan weirnotableto accommodate High Run off design flood of Kali Kuning river, while in the others control pointsare relatively safe.Keywords: Flood discharge, high runoff, Kali Kuning river,